Over expression of Recombinant CP3 Protein of Rice Tungro Spherical Virus in Prokaryotic Expression System (Bioremediation Science and Technology Research (e-ISSN 2289-5892), 2015)
Currently, serological based diagnosis of rice tungro disease (RTD) is being limited by theavailability of antisera. This study aims to produce recombinant protein from the coat protein(CP)3 of rice tungro spherical virus (RTSV) as a potential antigen in producing high titreantibodies for use in detection of RTD. Amplified RTSV CP3 gene of approximately 900 bpwas cloned into pETSUMO vector. The recombinant plasmid was transformed into cloning hostMach1â„¢-T1Â® E.coli cells and screened for recombinant gene in the correct orientation. PlasmidDNA from positive transformants was isolated and transformed into expression host BL21(DE3) E.coli cells. One positive clone was selected for large scale expression where theexpressed protein was purified and analysed by SDS-PAGE and Western blot. Thisrecombinant RTSV CP3 protein, 46 kDa in molecular mass with 6x His-tag and SUMO proteinfused to its N-terminal, was found to be antigenic when it reacted with our in-house generatedpolyclonal antibodies against tungro viruses.